Presence of Potential G‐Quadruplex RNA‐Forming Motifs at the 5′‐UTR of PP2Acα mRNA Repress Translation. (26th September 2019) - Pany, Sushree Prangya P.; Sapra, Mahak; Sharma, Jitendar; Dhamodharan, V.; Patankar, Swati; Pradeepkumar, P. I.
Abstract: RNA G‐quadruplex (G4)‐forming motifs present at the 5′‐UTR of the protein phosphatase ( PP2Ac ) gene are the regulatory targets of the fragile X mental retardation protein (FMRP), which is weakly expressed in Fragile X patients. Herein, we report that the existence of such G4‐forming sequence represses the translation of the PP2Acα gene. This study opens therapeutic avenues to design small molecule ligands that mimic the function of the FMRP. Abstract : Suppressed translation : A guanine‐rich sequence present at the 5′‐UTR of the PP2Acα mRNA represses the translation process by forming G‐quadruplex (G4) motifs (see figure). Small molecule ligands can mimic the Fragile X mental retardation protein (FMRP) by stabilizing the G4 structure.